Forbidden Visibility: Queer Activism, Shari‘a Sphere and Politics of Sexuality in Aceh - Ichwan, Moch. Nur (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
This article aims to explain why organized queer activism emerged in Aceh, but could endure only in about six years (from 2008 to 2014). It is argued that this has mainly caused by massive expansion of ‘shari‘a spheres’ since 2001 supported by national and local government and parliament legal-political back up and societal religio-cultural forces on the one hand, and weak nature of the queer movements as counterpublics, characterized with the inadequate resources mobilization, especially in leadership and in getting support from its social movement communities during the crises on the other hand. Shari‘a, which is heteronormative, have been used as discursive and embodied disciplinary power of sexuality for normalizing and excluding the queer (including lesbian, gay, bisexual, and transgender/LGBT). Their organized visibility triggered the issuance of the Qanun Jinayah in 2014, which includes punishment for same-sex activities. It caused them to dissolve their own queer organizations.